Pengembangan Produk Keripik Kelapa Skala Industri Kecil - Mohamad Awaludin; Nuri Andarwulan; Nur Wulandari (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2022)
XYZ is a small industrial scale coconut chips producer who wants to develop their products and market. This study aimed to describe ideal characteristic of coconut chips, develop XYZ product and their marketing strategy. The research used survey method by distributing online questionnaires to respondents, and sensory tests (CATA, RATA, hedonic) by untrained panelists. As quantitative descriptive research, it was conducted in four stages: consumer surveys, mapping of sensory attributes of coconut chips by PCA, product improvement, and development of marketing strategies through STPD analysis and business model canvas (BMC). The results showed that the market opportunity for coconut chips was still available and prospective. Crispness, sweet taste, sweet aftertaste, and caramel aroma were ideal product characteristics of coconut chips after mapping of sensory attributes from three competitor products and XYZ product. XYZ product weakness was corrected for its sweet taste attribute by reformulation to increase sweetness, and the selected formula used a ratio of weight of sugar and coconut chips 2:8 (w:w). Efforts to increase consumer interest in product need to be carried out through marketing strategies targeting young people and the target market for the middle class, as well as a differentiating in the use of natural ingredients without preservatives and artificial coloring.